External guide sequence technology: a path to development of novel antimicrobial therapeutics - Davies Sala, Carol Giselle (2015)
RNase P is a ribozyme originally identified for its role in maturation of tRNAs by cleavage of precursor tRNAs (pre-tRNAs) at the 5'-end termini. RNase P is a ribonucleoprotein consisting of a catalytic RNA molecule and, depending on the organism, one or more cofactor proteins. The site of cleavage of a pre-tRNA is identified by its tertiary structure; and any RNA molecule can be cleaved by RNase P as long as the RNA forms a duplex that resembles the regional structure in the pre-tRNA. When the antisense sequence that forms the duplex with the strand that is subsequently cleaved by RNase P is in a separate molecule, it is called an external guide sequence (EGS). These fundamental observations are the basis for EGS technology, which consists of inhibiting gene expression by utilizing an EGS that elicits RNase P-mediated cleavage of a target mRNA molecule. EGS technology has been used to inhibit expression of a wide variety of genes, and may help development of novel treatments of diseases, including multidrug-resistant bacterial and viral infections.